Interventions to treat cutaneous leishmaniasis in children: a systematic review - Uribe-Restrepo, Andrés; Cossio, Alexandra; Desai, Mayur M.; Dávalos, Diana; Castro, María del Mar (PLoS neglected tropical diseases, 2018)
Cutaneous leishmaniasis (CL) is a parasitic disease that causes chronic, often ulcerated, skin lesions that leave lifelong scars on the face or other visible areas. In some regions of the world, children represent a high proportion of cases. Treatment options for children are limited, and may require administration of poorly tolerated drugs. Despite the differences in responses to these drugs, treatment regimens for children are based on extrapolation of efficacy data in adults. We systematically reviewed the medical literature, searching for controlled studies assessing treatments for CL in children. Eight articles (461 patients aged 2-15 years) were included. None of the studies enrolled children <2 years of age. Identified treatments were miltefosine, systemic and intralesional meglumine antimoniate (MA), cryotherapy, and rifampicin. Sub-optimal quality and small sample sizes limit the generalizability of results from some of these studies. In general, for the Americas, oral miltefosine showed high efficacy, and in an Iranian study, intralesional MA showed higher efficacy than cryotherapy. This study provides evidence of the scarcity of data available to support treatment recommendations in children and of the unmet need to develop and test better treatment options for this vulnerable population.
Gesehen am 24.02.2020